Maternal Antibodies Elicited by Immunization With an O- Polysaccharide Glycoconjugate Vaccine Protect Infant Mice Against Lethal Salmonella Typhimurium Infection - Baliban, Scott M.; Curtis, Brittany; Amin, Mohammed N.; Levine, Myron Mike; Pasetti, Marcela F.; Simon, Raphael (Frontiers in Immunology, 2019)
Non-typhoidal Salmonella (NTS) are a leading cause of pediatric invasive bacterial infections in sub-Saharan Africa with high associated case fatality rates in children under five years old. We have developed glycoconjugate vaccines consisting of the lipid A-removed surface polysaccharide of NTS, core and O-polysaccharide (COPS), with the flagellar monomer protein (FliC) from the homologous serovar as the carrier. We previously established that COPS:FliC was immunogenic and protective when mice were primed either as adults or infants; however, the brief period of murine infancy precluded assessment of protection against invasive NTS (iNTS) disease in early life. In the present study, we used a mouse model of maternal immunization to study whether transmission of S. Typhimurium COPS:FliC-induced maternal antibodies could confer protection against lethal iNTS challenge in infant mice. We found here that anti-COPS and anti-FliC IgG were transferred to the offspring of COPS:FliC-immunized mice and sera from both vaccinated mothers and their litters mediated complement-dependent bactericidal activity in-vitro. Furthermore, two-week old infant mice born to immune mothers were robustly protected from challenge with an S. Typhimurium blood isolate from sub-Saharan Africa. The pre-clinical findings reported herein demonstrate that anti-COPS:FliC antibodies are sufficient for protection of murine infants against experimental S. Typhimurium infection. By underscoring the protective role of antibody, our data suggest that maintaining an adequate titer of protective anti-Salmonella antibodies during early life, either through pediatric or maternal COPS:FliC vaccination, may reduce iNTS disease in young children in sub-Saharan Africa.